PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH (ABITONIK) DAN MACAM PERBANDINGAN N,P,K DALAM PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max (L). Merril) VARIETAS WILIS - Furoidah, Nanik; Kusnadi, Wahid (JURNAL BIOSHELL, 2014)
The experiment was intended to determine the effect of concentration Abitonik and comparison of N, P and K in the fertilizer on the growth and yield of soybean varieties Wilis. Research methods in factorial randomized block design with basic patterns (RBD) 3x3 consisting of 2 factors and 3 replications. The treatment of each of these factors are: Factor Abitonik PGR concentration (Z) consists of 3 levels, namely Z0: without using abitonik (Control); Z1: Abitonik 0.5 ml per liter of water and Z2: Abitonik 1.0 ml per liter of water. Factors kinds of comparisons of N, P and K in fertilizers (P) consists of three levels: P1: comparison of N: P: K: 50:50:50; P2: Comparison of N: P: K: 50: 100: 175. The experimental data were analyzed by the F test (Fingerprint Variety) and followed by Ducan's Multiple Range Test 5%. The experimental results showed that the concentration Abitonik and comparison of N, P and K in fertilizers as well as the interaction between the two treatments very significant effect on plant height, number of branches on the main stem, number of pods per plant, number of pods per plant contains, the number of empty pods per plant and dry weight of 1,000 seeds. Concentration Abitonik very significant effect on plant height, number of branches on the main stem, number of pods per plant, number of pods per plant and weight of 1,000 dry beans. Concentration is the most appropriate Abitonik 1.0 ml per liter of water. Comparison of N, P and K in the fertilizer very significant effect on plant height, number of branches on the main stem, number of pods per plant, number of pods per plant and weight of 1,000 dry beans. The best comparison of N, P and K is 50: 100: 175. Interaction Abitonik concentration and ratio of N, P and K in the fertilizer very significant effect on plant height, number of branches on the main stem, number of pods per plant, number of pods per plant and 1,000 weight of dry beans. The best treatment combination is most appropriate Abitonik concentration is 1.0 ml per liter of water Abitonik and comparison of N, P and K in fertilizers 50: 100: 175.  Keywords: Concentration, growth regulators Abitonik, comparison of N, P, K in fertilizer, soybean ((Glycine max (L). Merrill)